2015
DOI: 10.1242/jcs.176651
|View full text |Cite
|
Sign up to set email alerts
|

Srv2/CAP is required for polarized actin cable assembly and patch internalization during clathrin-mediated endocytosis

Abstract: The dynamic assembly and disassembly of actin filaments is essential for the formation and transport of vesicles during endocytosis. In yeast, two types of actin structures, namely cortical patches and cytoplasmic cables, play a direct role in endocytosis, but how their interaction is regulated remains unclear. Here, we show that Srv2/CAP, an evolutionarily conserved actin regulator, is required for efficient endocytosis owing to its role in the formation of the actin patches that aid initial vesicle invaginat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The movement of this Pan1p/actin aggregate in pan1-18TA was sensitive to SMIFH2 but not CK-666, suggesting that the aberrant structure associates with actin cables ( Figure 4—figure supplement 1B–E ). In a recent study, we showed that ~85% of endocytic vesicles were internalized along actin cables at the internalization step of endocytosis ( Toshima et al, 2015 ). Here we show that in this step, Pan1-mCherry-labeled vesicles in wild-type cells associated with actin cables for ~4.6 s and moved on cables about 0.4 μm after internalization ( Figure 4A,B,C ).…”
Section: Resultsmentioning
confidence: 99%
“…The movement of this Pan1p/actin aggregate in pan1-18TA was sensitive to SMIFH2 but not CK-666, suggesting that the aberrant structure associates with actin cables ( Figure 4—figure supplement 1B–E ). In a recent study, we showed that ~85% of endocytic vesicles were internalized along actin cables at the internalization step of endocytosis ( Toshima et al, 2015 ). Here we show that in this step, Pan1-mCherry-labeled vesicles in wild-type cells associated with actin cables for ~4.6 s and moved on cables about 0.4 μm after internalization ( Figure 4A,B,C ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that CAP protein interacts directly with V-ATPase and acts as a general regulator of endocytosis in Dictyostelium (Sultana et al, 2005). A recent study has shown that Srv2/Cap1 is responsible for efficient endocytosis by aiding initial vesicle invagination and movement (Toshima et al, 2016). Some of the defects observed in the Fgcap1 mutant may be independent of cAMP signalling, but related to the role of FgCAP1 in endocytosis in F. graminearum.…”
Section: Discussionmentioning
confidence: 99%
“…Srv2 was previously known to regulate actin recycling and severing. Both polarized actin cable assembly and patch formation are the major regulatory functions of Srv2/CAP (Toshima et al., 2016). Our results of SRV2 deletion and mutant alleles bring the regulatory mechanisms of mitochondria and actin dynamics together.…”
Section: Discussionmentioning
confidence: 99%